ANALISIS PEMETAAN BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO - Kusumaningtyas, Yona; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2016)
Organization Culture is need to be developed and adapted with the developments and changes of the organization. Nowadays, many companies do not understand the importance of organization culture as a fundamental factor in the company. Faculty of Economics and Business Universitas Diponegoro have the vision, mission, values, and goals to be achieved. With the mapping of cultural profile of current and future expectations may be one input for an institution to prepare for the change and understand whether the vision, mission, and values that have been defined it is understood and preserved as the organization's culture.This research was conducted by survey method using OCAI (Organizational Culture Assessment Instrument). The survey conducted on alumni, students, staff, and faculty with a sample size of each stratum 25 people. So great the entire sample was 100 people. This research uses descriptive quantitative approach so as to reveal and analyze the cultural profile FEB Undip current and expected in the next few years.The results obtained from this study showed a difference between the perception of the current culture of alumni, students, staff, and faculty. Alumni, staff, and faculty feel that the dominant culture of the company is the culture clan. Meanwhile, students feel the current dominant culture is a culture of hierarchy. There are cultural similarities expected by all stakeholders ie culture clan. There seems to be a trend toward more powerful clan culture as a type of culture is expected. This cultural profile picture FEB Undip can be used for decision making in accordance with the vision, mission and objectives of the FEB Undip.